In-house environmental factors and childhood acute respiratory infections in under-five children: a hospital-based matched case-control study in Bangladesh - Moktarul Islam; Kariul Islam; Koustuv Dalal; Mohammad Delwer Hossain Hawlader (BMC, 2024)
Abstract Background Acute respiratory infection (ARI) is one of the leading causes of morbidity and mortality among children under five globally, particularly in regions like South Asia and sub-Saharan Africa. Bangladesh has made substantial progress in reducing child mortality, yet pneumonia remains a significant contributor to under-five deaths. This study aimed to investigate the association between in-house environmental factors and childhood ARI, considering factors such as household crowding, smoking, and sanitation facilities. Methods This case-control study was conducted at a tertiary-level children's hospital in Dhaka, Bangladesh, from March to September 2019. The study included children aged 6-59 months. Cases were children with ARI symptoms, while controls were children without such symptoms. Rigorous matching by age and gender was employed to ensure comparability. Data were collected through structured questionnaires, and bivariate and conditional logistic regression analyses were performed. Results Several household environmental factors were significantly associated with childhood ARIs. Children from overcrowded households (AOR = 2.66, 95% CI = 1.52-4.71; p < 0.001), those using unclean cooking fuels (OR = 2.41, 95% CI: 1.56, 3.73; p = < 0.001), those exposed to in-house smoking (AOR = 1.74, 95% CI = 1.01, 3.05; p = 0.04) and those with unimproved sanitation facilities faced higher odds (AOR = 4.35, 95% CI = 2.14-9.26) of ARIs. Additionally, preterm birth and higher birth order were associated with an increased risk of ARI. In contrast, exclusive breastfeeding was a protective factor. Conclusion In-house environmental factors, including sanitation, crowding and in-house smoking, significantly influence childhood ARIs. Additionally, birth order and preterm birth play a crucial role. Promoting exclusive breastfeeding is associated with a lower ARI risk among under-five children in Bangladesh. These findings can guide interventions to reduce ARIs in low-income regions, particularly in South Asia.